Distance Detection Technique Using Enhancing Inverse Perspective Mapping - Wongsaree, Preaw; Sinchai, Sakkarin; Wardkein, Paramote; Koseeyaporn, Jeerasuda (My University, 2018)
This paper presents a distance determination technique using an image from the single forward camera. Since too dark or too bright of the image and non-linear relation between height of the object and distance from the camera have effect on the performance of the detection process. Therefore, automatic brightness adjustment and inverse perspective mapping (IMP) is applied in the proposed scheme. In addition, region of interest (ROI) determination is used to decrease the processing time. The experimental results confirm that the proposed technique can detect distance of the object in front of the car where the error is 7.96%.
Keywords: component; distance detection; gamma correction; inverse perspective mapping; opencv